(3QSGdI aj JMbjb GdcdGe Ydi cdeI YQaGJ hJUQjagGs - (3CHh GdMSf GdYUGejs ((3YKeGf Hf SdjeGfs)
(3ChdgG (B:s
(3GYde Cf YQaGJ LeY Sej Hg Gdehba cGPQYGJ hGNJda ajg aGNJGQ UGMH GdcTGa Cfg efUQa dCf GdJGA GdJj aj daXg djSJ ddJCfjK hEfeG gj eY GdCda GdJj LeY GdeDfK (B((3cPG(B) (3hdG jLhR JCfjKg HJGA ebOQIs
(3BNQgG (B:s
(3deG efY ef QLhYg cGf dYhV efg adeG efY Jfhjf GdebGHdI Jfhjf GdUQa HGdcdjI de JMJL dEHQGe efYg Edi ESbGW GdcSQ hgPG GdPj PgH Edjg GdbGVj ePgH GdLeghQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdUQas